Cell-IQ visualization of motility, cell mass, and osteogenic differentiation of multipotent mesenchymal stromal cells cultured with relief calcium phosphate coating; Doklady Biochemistry and Biophysics; Vol. 476, iss. 1 - Litvinova L. S.; Shupletsova V. V.; Yurova K. A.; Khaziakhmatova O. G.; Todosenko N. M.; Khlusova M. Yu.; Slepchenko G. B. Galina Borisovna; Cherempey E. G. Elena Gennadjevna; Sharkeev Yu. P. Yury Petrovich; Komarova E. G. Elena Gennadjevna; Sedelnikova M. B. Mariya Borisovna; Malashenko V. V.; et al. (Biochemistry, Biophysics, and Molecular Biology, 2017)
Title screen